2022
DOI: 10.17582/journal.pjz/20191211071205
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenetic and Mutational Analysis of Neuraminidase of Avian Influenza A (H9N2) Virus of B2- Sub Lineage, Isolated from Commercial Poultry Pakistan

Abstract: This paper records a new distribution of long-billed vulture in the Sindh Province of Pakistan. Existing literature on long-billed vultures provides the distribution and status of this vulture in Sindh Province but does not cover the western mountainous eco-region. IUCN Pakistan's team conducted a pre-monsoon baseline survey in the province in the dry season in June 2019 and another survey in the vulture breeding season, in February 2020. Methodology included direct field observations and interviews of local c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Due to variable conditions that can influence poultry susceptibility to infections (20)(21), further investigation was carried out to understand the impact of chIFITM3 against a pre-determined clinical dose of H5N1. The results revealed that the clinical dose of H5N1 considerably reduced the clinical outcome when used in transgeneoverexpressing chicks, which indicates the ability of innate immunity to protect against HPAIV H5N1.…”
Section: Discussionmentioning
confidence: 99%
“…Due to variable conditions that can influence poultry susceptibility to infections (20)(21), further investigation was carried out to understand the impact of chIFITM3 against a pre-determined clinical dose of H5N1. The results revealed that the clinical dose of H5N1 considerably reduced the clinical outcome when used in transgeneoverexpressing chicks, which indicates the ability of innate immunity to protect against HPAIV H5N1.…”
Section: Discussionmentioning
confidence: 99%